2021
DOI: 10.3390/ijerph18094691
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Regulates TNFα and IL-6 Expression to Counteract Inflammation in Cystic Fibrosis Patients

Abstract: Background: Cystic fibrosis (CF) is one of the most common inherited diseases. It is characterised by a severe decline in pulmonary function associated with metabolic perturbations and an increased production of inflammatory cytokines. The key role of physical activity (PA) in improving the health status of CF patients and reducing lung function decline has recently been demonstrated. This study evaluated interleukin-6 (IL-6) and tumour necrosis factor α (TNFα) expression in two subgroups of CF patients classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Our exercise rehabilitation program did not change any of the inflammatory markers analyzed. On the other hand, another study demonstrated that physical activity modulates IL-6 and TNF- levels in patients with CF ( 29 ). However, Nigro et al ( 29 ) evaluated patients who performed supervised physical activity regularly for three years before the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our exercise rehabilitation program did not change any of the inflammatory markers analyzed. On the other hand, another study demonstrated that physical activity modulates IL-6 and TNF- levels in patients with CF ( 29 ). However, Nigro et al ( 29 ) evaluated patients who performed supervised physical activity regularly for three years before the study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another study demonstrated that physical activity modulates IL-6 and TNF- levels in patients with CF ( 29 ). However, Nigro et al ( 29 ) evaluated patients who performed supervised physical activity regularly for three years before the study. Similarly, other studies showed that brief and moderate exercise can improve inflammatory cytokines in CF ( 6 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…LPS stimulation is capable of activating the inflammatory cascades, such as TNF-α and IL-6 (33,34). TNF-α and IL-6 are representative inflammatory cytokines that participate in the progression of various diseases, such as diabetes, sepsis, cardiovascular diseases, fibrosis, and cancers (35)(36)(37)(38). The abnormal serum levels of IL-10, IL-6, IL-1β, and TNF-α are proposed as potential diagnostic biomarkers for community-acquired pneumonia and coronavirus disease infection (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…We know from other chronic lung diseases, such as cystic fibrosis (CF), that physical activity is associated with improved sputum expectoration. Particularly beneficial are higher intensity activities followed by respiratory physiotherapy [10,11].…”
Section: Introductionmentioning
confidence: 99%